Level of knowledge and practice regarding dietary intake among patient with End Stage Renal Disease (ESRD) in Hospital Universiti Sains Malaysia (HUSM) - Hamzah, Siti Wajihah (2020)
This research is about the knowledge and practice regarding dietary intake among patients with ESRD in HUSM. Diet plays an important role in slowing down kidney problems and dialysis. The main objective of this study was to determine the knowledge and practices regarding dietary intake in HUSM. A cross-sectional study was conducted on 20 patients from ward 7 Utara, 7 Selatan, Haemodialysis Unit. The majority of 18 (90%) respondents indicated an intermediate knowledge level in dietary intake. Similar results also found that almost 90% of respondents had moderate dietary practices. Meanwhile, there was no significant difference between the level of knowledge and practice. In conclusion, it is very important for ESRD patients to know the importance of the renal diet and its benefits. Patients can gain more benefit from proper dietary guidance and management.